On the origin of deletions and point mutations in Duchenne muscular dystrophy: most deletions arise in oogenesis and most point mutations result from events in spermatogenesis. Issue 3 (March 1994) - Grimm, T; Meng, G; Liechti-Gallati, S; Bettecken, T; Müller, C R; Müller, B
Abstract : We present the results of a study of the rate and origin of mutations in Duchenne muscular dystrophy (DMD). Depending on the type of mutation (deletion/duplication or point mutation) present in the patient, there are widely varying ratios of male to female mutation rates. In deletions, the male mutation rate is only 30% of the female one. In non-deletional/non-duplicational mutations (presumably containing a high proportion of point mutations) the male mutation rate is at least 2.2 as high as the female one and probably much higher. Allowing for the presence of autosomal recessive phenocopies we find that k in non-deletional/non-duplicational mutations is 40.3. These findings mean that the vast majority of deletions arise in oogenesis, while most point mutations stem from spermatogenesis. Previous investigations have shown that in other diseases and genes, most notably haemophilia B and A, but also the ZFY and ZFX genes, the male mutation rate for point mutations tends to be higher than the female one. Our results can be seen as a confirmation of this for the special case of DMD. The influence on risk figures is considerable. As an example, the risk of the mother of an isolated case of DMD without an apparent structural anomaly of the gene of being a carrier increases from 67% to at least 76%. Given the estimate of 40.3 for k, allowing for the presence of autosomal recessive phenocopies mentioned above, it increases even further to 98%. However, as confidence intervals are still large, more data are needed to improve the estimates. Germinal mosaicism in this context is discussed.